ROLE OF PHRASEOLOGICAL UNITS IN LINGUISTICS - Muzaffarova Aziza,; Khakimbayeva O.K., (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This article examines the concept of phraseological units, their place in the language system, and their significance in communication. Phraseological units represent a special layer of vocabulary characterized by stability, figurative meaning, and expressive power. They reflect the cultural values, historical experience, and worldview of a nation. The paper also explores different types of phraseological units, their semantic and structural features, and their practical use in both spoken and written discourse. In addition, attention is given to their role in language learning and teaching, as well as their importance in developing communicative competence.